Uncommon Trimethoxylated Flavonol Obtained from Rubus rosaefolius Leaves and Its Antiproliferative Activity. (14th December 2015) - Petreanu, Marcel; Ferreira, Emili Kamila; Sagaz, Ana Paula M.; Vendramini-Costa, Débora B.; Ruiz, Ana Lúcia T. G.; De Carvalho, João Ernesto; Campos, Adriana; Cechinel Filho, Valdir; Delle Monache, Franco; Niero, Rivaldo
Abstract : This study shows the evaluation the antiproliferative effect of the extract, fractions, and uncommon compounds isolated from R. rosaefolius leaves. The compounds were identified by conventional spectroscopic methods such as NMR-H 1 and C 13 and identified as 5, 7-dihydroxy-6, 8, 4′-trimethoxyflavonol (1 ), 5-hydroxy-3, 6, 7, 8, 4′-pentamethoxyflavone (2 ), and tormentic acid (3 ). Both hexane and dichloromethane fractions showed selectivity for multidrug-resistant ovary cancer cell line (NCI-ADR/RES) with total growth inhibition values of 11.1 and 12.6  μ g/ml, respectively. Compound1 also showed selective activity against the same cell line (18.8  μ g/ml); however, it was especially effective against glioma cells (2.8  μ g/ml), suggesting that this compound may be involved with the in vitro antiproliferative action.